The difference of cubes is a binomial algebraic expression of the form a3 - b3, where the terms a and b can be real numbers or algebraic expressions of various types. An example of a difference of cubes is: 8 - x3, since 8 can be written as 23.
Geometrically we can think of a large cube with side a, from which the small cube with side b is subtracted, as illustrated in figure 1:
The volume of the resulting figure is precisely a difference of cubes:
V = a3 - b3
To find an alternative expression, it is observed that this figure can be decomposed into three prisms, as shown below:
A prism has a volume given by the product of its three dimensions: width x height x depth. In this way, the resulting volume is:
V = a3 - b3 = atwo.b + b3 + a.btwo
The factor b it is common to the right. Furthermore, in the figure shown above, it is particularly true that:
b = (a / 2) ⇒ a = b + b
Therefore it can be said that: b = a - b. Thus:
to3 - b3 = b (atwo + btwo +a.b) = (a-b) (atwo + a.b + btwo)
This way of expressing the difference of cubes will prove to be very useful in many applications and would have been obtained in the same way, even if the side of the missing cube in the corner was different from b = a / 2.
Note that the second parenthesislooks a lot like the remarkable product of the square of the sum, but the cross term is not multiplied by 2. The reader can develop the right side to verify that it is actually obtained to3 - b3.
Article index
There are several differences of cubes:
1 - m6
to6b3 - 8z12Y6
(1/125) .x6 - 27 and9
Let's analice each one of them. In the first example, the 1 can be written as 1 = 13 and the term m6 remains: (mtwo)3. Both terms are perfect cubes, therefore their difference is:
1 - m6 = 13 - (mtwo)3
In the second example the terms are rewritten:
to6b3 = (atwob)3
8z12Y6 = 23 (z4)3 (Ytwo)3 = (2z4Ytwo)3
The difference of these cubes is: (atwob)3 - (2z4Ytwo)3.
Finally, the fraction (1/125) is (1/53), x6 = (xtwo)3, 27 = 33 and and9 = (and3)3. Substituting all this in the original expression, you get:
(1/125) .x6 - 27y9 = [(1/5) (xtwo)]3 - (3y3)3
Factoring the difference of cubes simplifies many algebraic operations. To do this, it is enough to use the formula deduced above:
Now, the procedure to apply this formula consists of three steps:
- First, the cube root of each of the terms of the difference is obtained.
- Then the binomial and the trinomial that appear on the right side of the formula are constructed.
- Finally, the binomial and the trinomial are substituted to obtain the definitive factorization.
Let's illustrate the use of these steps with each of the cube difference examples proposed above and thus obtain its factored equivalent.
Factor the expression 1 - m6 following the steps outlined. We start by rewriting the expression as 1 - m6 = 13 - (mtwo)3 to extract the respective cube roots of each term:
Next, the binomial and the trinomial are constructed:
a = 1
b = mtwo
Then:
a - b = 1 - mtwo
(totwo +a.b + btwo) = 1two + 1.mtwo + (mtwo)two = 1 + mtwo + m4
Finally it is substituted in the formula a3 - b3 = (a-b) (atwo +a.b + btwo):
1 - m6 = (1 - mtwo) (1 + mtwo + m4)
Factorize:
to6b3 -8z12Y6 = (atwob)3 - (2z4Ytwo)3
Since these are perfect cubes, the cube roots are immediate: atwob and 2z4Ytwo, hence it follows that:
- Binomial: atwob - 2z4Ytwo
- Trinomial: (atwob)two + totwob. 2z4Ytwo + (totwob + 2z4Ytwo)two
And now the desired factorization is constructed:
to6b3 -8z12Y6 = (atwob - 2z4Ytwo). [(totwob)two + totwob. 2z4Ytwo + (totwob + 2z4Ytwo)two] =
= (atwob - 2z4Ytwo). [to4btwo + 2ndtwob.z4Ytwo + (totwob + 2z4Ytwo)two]
In principle, the factoring is ready, but it is often necessary to simplify each term. Then we develop the remarkable product -square of a sum- that appears at the end and then add like terms. Remembering that the square of a sum is:
(x + y)two = xtwo + 2xy + andtwo
The notable product on the right is developed like this:
(totwob + 2z4Ytwo)two = a4btwo + 4thtwob.z4Ytwo + 4z8Y4
Substituting the expansion obtained in the factorization of the difference of cubes:
to6b3 -8z12Y6 = (atwob - 2z4Ytwo). [to4btwo + 2ndtwob.z4Ytwo + to4btwo + 4thtwob.z4Ytwo + 4z8Y4] =
Finally, grouping like terms and factoring the numerical coefficients, which are all even, we obtain:
(totwob - 2z4Ytwo). [2a4btwo + 6thtwob.z4Ytwo + 4z8Y4] = 2 (atwob - 2z4Ytwo). [to4btwo + 3rdtwob.z4Ytwo + 2z8Y4]
Factor (1/125) .x6 - 27y9 it is much simpler than the previous case. First the equivalents of a and b are identified:
a = (1/5) xtwo
b = 3y3
Then they are directly substituted in the formula:
(1/125) .x6 - 27y9 = [(1/5) xtwo - 3y3]. [(1/25) x4 + (3/5) xtwoY3 + 9y6]
The difference of cubes has, as we have said, a variety of applications in Algebra. Let's see some:
Solve the following equations:
a) x5 - 125 xtwo = 0
b) 64 - 729 x3 = 0
First the equation is factored in this way:
xtwo (x3 - 125) = 0
Since 125 is a perfect cube, the parentheses are written as a difference of cubes:
xtwo . (x3 - 53) = 0
The first solution is x = 0, but we find more if we do x3 - 53 = 0, then:
x3 = 53 → x = 5
The left side of the equation is rewritten as 64 - 729 x3 = 43 - (9x)3. Therefore:
43 - (9x)3 = 0
Since the exponent is the same:
9x = 4 → x = 9/4
Factor the expression:
(x + y)3 - (x - y)3
This expression is a difference of cubes, if in the factoring formula we note that:
a = x + y
b = x- y
Then the binomial is constructed first:
a - b = x + y - (x- y) = 2y
And now the trinomial:
totwo + a.b + btwo = (x + y)two + (x + y) (x-y) + (x-y)two
Notable products are developed:
(x + y)two = xtwo + 2xy + andtwo
(x + y) (x-y) = xtwo- Ytwo
(x- y)two = xtwo - 2xy + andtwo
Next you have to substitute and reduce like terms:
totwo + a.b + btwo = xtwo + 2xy + andtwo+ xtwo- Ytwo+ xtwo - 2xy + andtwo = 3xtwo + Ytwo
Factoring results in:
(x + y)3 - (x - y)3 = 2y. (3xtwo + Ytwo)
Yet No Comments